7. POLITIK INDONESIA PASKA ORBA : SIAPKAH UNTUK PERUBAHAN YANG LEBIH BAIK? - Harsasto, Priyatno (FORUM, 2007)
Indonesian political system has changed from authoritarian regime of Soeharto to a more democratic one. The new Oder political system has restricted power and participation to a small portion of the population who are high-ranking officers in the army and the bureaucracy. This system of government has been eliminated by reformist movement in the late of 1990s. However, while the structure of government has changed, government is still rooted in a personalized system which shy away the possibility of bureaucracy reform. There is a need for a pro-active leadership to amend the structural weakness of the state.